AYAT AHKAM DALAM EKONOMI SYARIAH - J, Roudotul Jannah; Gallyn Ditya Manggala; Sheny Yulianty; Badawi Murai (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2025)
The number of verses in the Qur'an has different opinions among scholars, the factor behind the disparity in the number of verses is the difference among those who listened to the Prophet's recitation, SAW. regarding waqf and washal. Regarding the number of ahkam verses, there is also ikhtilaf among scholars, the difference is caused by the perception of the criteria for the legal verses themselves, the reality does show that certain verses, on the one hand reflect legal verses, but on the other hand indicate other groups of verses. There are scholars who count the number of ahkam verses less, namely 150 verses, this may be because they only count those that really explain the law, in the sense of normative law only. There are scholars who count the number of ahkam verses reaching 900, some even count up to 1100 verses, this calculation is considered more realistic. because in reality, there are not a few legal istinbath taken from verses themed qashas (stories), verses of proverbs (parables) and even verses with other themes, but in the syar`i khitab it is still related to the actions of mukallaf people contained in the Qur'an and sunnah, both explicitly and implicitly. While some say that the number of economic and financial verses is only 10 verses and some say it reaches 400 verses, this is because some use verses as evidence in all aspects of the economy, both consumption, production, distribution, agriculture, fisheries, employment and other aspects, even though only implicitly.